Philosophy Of Values: Ethics And Aesthetics: Filsafat Nilai: Etika dan Estetika - Apriani, Sela; Heri, Asep; Jenuri (Universitas Muhammadiyah Sidoarjo, 2025)
Background: Contemporary education requires a holistic foundation that encompasses moral clarity and aesthetic sensitivity to guide learners in navigating complex social and cultural realities. Specific Background: Although ethics and aesthetics are central to value philosophy, educational practice often separates moral instruction from aesthetic experience, resulting in fragmented character formation. Knowledge Gap: Limited conceptual work explains how these two value dimensions operate as a unified foundation for character development, particularly within the context of modern schooling. Aim: This study examines the philosophical relationship between ethics and aesthetics and articulates how their integration contributes to character formation in contemporary education. Results: Analysis of classical and modern philosophical sources demonstrates that ethical values gain depth when expressed through aesthetic experiences, while aesthetic expression becomes meaningful when grounded in moral virtue. This unity supports learning that is reflective, compassionate, and imaginative. Novelty: The study offers a conceptual synthesis linking axiology, ethics, and aesthetics to Indonesia’s current educational model, emphasizing harmony between moral reasoning and aesthetic expression. Implications: Integrating these dimensions encourages curriculum, pedagogy, and school culture that cultivate morally aware and aesthetically sensitive learners equipped to face twenty-first-century challenges. Highlights: • Ethics and aesthetics function as integrated value dimensions in character formation.• Aesthetic experience deepens learners’ moral sensitivity and reflective awareness.• Unified ethical-aesthetic approaches support holistic development in contemporary education. Keywords: Value Philosophy, Ethics, Aesthetics, Character Education, Axiology